THE EFFECTIVENESS OF AUDIO-LINGUAL METHOD ON STUDENTS’ PRONUNCIATION ABILITY AT THIRD SEMESTER IN THE UNIVERSITY OF PASIR PENGARAIAN - Eripuddin Eripuddin; Evi Kasyulita (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Abstract. Studying pronunciation is little bit hard than other skill cause need practice and need new method to engage students’ ability. For those the researcher apply audio-lingual method to engage students’ pronunciation ability. This research aims to see the effect of audio-lingual method to students’ pronunciation. This research is quasi experimental research; nonequivalent control group design. They are thirdly eight students. Twenty students are in regular class and eighteen students are in non-regular class. Experiment class is taught Audio-lingual method   and   Control   class   is   taught   conventional technique. The data will be analyzed by using independent t-test. The research finding is expected enrich theories about teaching method in pronunciation. Keywords. Audio-lingual method, Students; pronunciation, Third semester, University of Pasir Pangaraian